THE INFLUENCE OF ROE, EQUITY, AND DER ON COMPANY VALUE IN START UP COMPANIES PERIOD 2019-2021 - Cyndi Adeline Br. Purba; Yeni Ariesa; Cut Diah Paramita; Juli Meliza (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
As an era advances, the role of humans is increasingly being replaced by technology. Start-up companies are clear evidence that technology has become increasingly advanced in this world. The aim of this research was to test how much influence roe, equity and der have on company value in start-up companies registered on Yahoo Finance for the 2019-2021 period. This type of research uses a quantitative approach. Yahoo finance is a source of obtaining data used in research with data analysis using eviews 12. The amount of data used is 17 start-up companies on Yahoo Finance. Company value is important information for investors when investing in a company. Company profits are influenced by many factors that can increase which become benchmarks for investors